Acupuncture for treatment of insomnia: An overview of systematic reviews. (February 2019) - He, Wenbo; Li, Meixuan; Zuo, Liqian; Wang, Meng; Jiang, Lili; Shan, Houqian; Han, Xue; Yang, Kehu; Han, Xuemei
Highlights: The overview of System Reviews/Meta-analysis is a comprehensive research method for evaluating factors related to the treatment, etiology, diagnosis and prognosis of the same health problem. PubMed, EMBASE, Web of science, Cochrane library, Chinese Biomedical Databases (CBM), VIP and China National Knowledge Infrastructure (CNKI) were retrieved and relevant data were extracted. The methodological quality evaluation and outcome index quality evaluation of the systematic evaluation were carried out, and the effectiveness and safety of acupuncture in treating insomnia were analyzed systematically. Our overview showed that acupuncture may be beneficial to insomnia patients. Based on the current evidence and the safety of acupuncture, there was a case for the use of acupuncture as an adjunctive therapy in insomnia. Abstract: Purpose: To evaluate the reliability of the methodological quality and outcome measures of systematic review (SR) /meta-analysis (MA) of acupuncture for insomnia. Methods: We conducted a comprehensive literature search for SRs with MAs in seven international and Chinese databases. Two reviewers independently extracted data and assessed the methodological quality of the reviews according to the Assessing the Methodological Quality of Systematic Reviews 2 (AMSTAR-2), the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) was used to rate the quality of evidence. Results: Thirty-four reviews were included. The AMSTAR-2 score showed that most of the included studies were of low methodological quality and included only two high-quality literatures. The lowest score were the item 10 (all the studies didn't report on the sources of funding for the studies included in the review), item 7(32 studies didn't provide a list of excluded studies and justify the exclusions) and item 3 (27 studies didn't explain their selection of the study designs for inclusion in the review). Conclusion: Most of the reviews included suggested that the acupuncture group was more effective than the control group in the treatment of insomnia, but the methodological quality of most of the studies and the quality of evidence were low.